The effect of childhood trauma on the severity of obsessive-compulsive symptoms: A systematic review. (October 2021) - Destrée, Louise; Brierley, Mary-Ellen E.; Albertella, Lucy; Jobson, Laura; Fontenelle, Leonardo F.
Abstract: Background: Childhood trauma is associated with a range of psychiatric disorders, including obsessive-compulsive disorder (OCD). However, our understanding of the different types of childhood trauma and its impact on the different types and severity of obsessive-compulsive symptoms (OCS) is still in its infancy. Aims: We conducted a systematic review to synthesise the current knowledge on the possible relationships between childhood trauma and obsessive-compulsive symptoms in clinical and non-clinical populations. Methods: We systematically searched four electronic databases for studies reporting on childhood trauma and OCS severity. Subsequently, we qualitatively synthesised results of eligible studies and effect sizes were also calculated. Results: Twenty-four studies were included in this systematic review. Most studies used OCD samples ( k = 16), with a few studies using a sample comprising of a range of psychiatric disorders ( k = 6) and some studies using a general community sample ( k = 2). Overall, there was support for a significant relationship between childhood trauma and OCS severity (8 out of 16 of the studies using OCD clinical samples, both studies using general population samples, and 5 out of 6 studies used mixed psychiatric samples). Conclusions: We found evidence of a significant relationship between exposure to childhood trauma and OCS severity across clinical and non-clinical populations. Our results also suggest that a range rather than a single type of childhood trauma was associated with OCD.